Effects of single and repeated shock wave application on the osteogenic differentiation potential of human primary mesenchymal stromal cells and the osteoblastic cell line MG63 in vitro - Haddouti, El-Mustapha; Reinhardt, Nina; Ossendorff, Robert; Burger, Christof; Wirtz, Dieter C.; de la Fuente, Matias; Schildberg, Frank A. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Extracorporeal shock wave therapy is a non-invasive and effective option for treating various musculoskeletal disorders. Recent literature indicates that the parameters for extracorporeal shock wave therapy, such as the optimal intensity, treatment frequency, and localization, are yet to be determined. Studies reporting on the effects of shock wave application on primary mesenchymal stromal cells (MSCs) as well as osteoblastic cell lines in vitro are barely available and not standardized. Methods: In this study, we designed a special setup to precisely expose primary MSCs and the osteoblastic cell line MG63 to shock waves and subsequently analyzed the resulting cellular responses using standardized protocols to investigate their viability, proliferation behavior, cytokine secretion, and osteogenic differentiation potential in vitro. The shock wave transducer was coupled to a specifically designed water bath containing a 5 mL tube holder. Primary human MSCs and MG63 cells were trypsinated and centrifuged in a 5 mL tube and exposed to single and repeated shock wave application using different intensities and numbers of pulses. Results: Single treatment of MSCs using intensities 5, 10, 15, and 20 and pulse numbers 100, 250, 500, 750, and 1,000 at a constant pulse repetition frequency of 1 Hz resulted in a decreased viability and proliferation of both cell types with an increase in the intensity and number of pulses compared to controls. No significant difference in the osteogenic differentiation was observed at different time intervals in both cell types when a single shock wave application was performed. However, repeated shock wave sessions over three consecutive days of primary MSCs using low intensity levels 0.1 and 1 showed significant osteogenic differentiation 4-fold higher than that of the extracted Alizarin Red S at day 14, whereas MG63 cells showed no significant osteogenic differentiation compared to their corresponding controls. More specifically, repeated shock wave application triggered a significant downregulation of COL1A1, upregulation of RUNX2, and sustained increase of OCN in primary MSCs but not in the cell line MG63 when induced toward the osteogenic differentiation. Discussion: The effects of shock wave application on MSCs make it an effective therapy in regenerative medicine. We established a protocol to analyze a standardized shock wave application on MSCs and were able to determine conditions that enhance the osteogenic differentiation of MSCs in vitro.